Physical and Mechanical Properties of Oriented Strand Board from Three Species of Plantation Forests at Various Resin Contents - Muhammad Iqbal Adi Baskara; Doni Hapsoro; Muhammad Iqbal Maulana; Marwanto; Denni Prasetia; Wahyu Hidayat; Muhammad Adly Rahandi Lubis; Nam Hun Kim; Fauzi Febrianto (Jurnal Sylva Lestari, 2022)
The objective of this study was to determine the physical and mechanical properties of oriented strand board (OSB) from three wood species of plantation forests, i.e., Afrika (Maesopsis eminii), mangium (Acacia mangium), and sengon (Paraserianthes falcataria) at various resin contents. OSB was made with a shelling ratio (face:core:back) of 1:2:1 and a target density of 0.6 g/cm3. Methylene diphenyl di-isocyanate (MDI) adhesive was used with 3%, 5%, and 7% resin contents. The physical and mechanical properties were evaluated based on JIS A 5908:2003 standard and the values were compared with CSA 0437.0 (Grade O-1) standard. The results show that the physical and mechanical properties of the OSB were improved as the resin content increased for all wood species. OSB prepared from Afrika and mangium wood strands with 7% resin content showed better physical and mechanical properties than the other OSBs. Thickness swelling of OSB prepared from three wood species had met the CSA O437.0 (Grade O-1) standard. All OSBs produced in this experiment met the standard for MOR parallel and perpendicular to the grain. OSB from three wood species with a 5% and 7% resin content met the standard for MOE perpendicular to the grain. Only mangium OSB with a resin content of 7% met the standards for MOE parallel to the grain. Afrika OSB with 5% and 7% resin content, mangium OSB with 5% resin content, and sengon OSB with 3% and 7% resin content met the standard for the internal bond. Keywords: Acacia mangium, Maesopsis eminii, Methylene diphenyl di-isocyanate, Oriented strand board, Paraserianthes falcataria